Escherichia coli out in the cold: Dissemination of human-derived bacteria into the Antarctic microbiome. (August 2016) - Power, Michelle L.; Samuel, Angelingifta; Smith, James J.; Stark, Jonathon S.; Gillings, Michael R.; Gordon, David M.
Abstract: Discharge of untreated sewage into Antarctic environments presents a risk of introducing non-native microorganisms, but until now, adverse consequences have not been conclusively identified. Here we show that sewage disposal introduces human derived Escherichia coli carrying mobile genetic elements and virulence traits with the potential to affect the diversity and evolution of native Antarctic microbial communities. We compared E . coli recovered from environmental and animal sources in Antarctica to a reference collection of E. coli from humans and non-Antarctic animals. The distribution of phylogenetic groups and frequency of 11 virulence factors amongst the Antarctic isolates were characteristic of E. coli strains more commonly associated with humans. The rapidly emerging E. coli ST131 and ST95 clones were found amongst the Antarctic isolates, and ST95 was the predominant E. coli recovered from Weddell seals. Class 1 integrons were found in 15% of the Antarctic E. coli with 4 of 5 identified gene cassette arrays containing antibiotic resistance genes matching those common in clinical contexts. Disposing untreated sewage into the Antarctic environment does disseminate non-native microorganisms, but the extent of this impact and implications for Antarctic ecosystem health are, as yet, poorly understood. Graphical abstract: Highlights: Human sewage is a conduit for microbial dissemination and gene pollution in Antarctica. Human and avian extra-intestinal pathogenic Escherichia coli (ST95) were isolated from Antarctic seals. E. coli ST131 was detected in Antarctic marine ecosystems. Class 1 integrons containing multiple antibiotic resistance cassettes were detected in E. coli . Genetic pollution provides a measureable impact of sewage disposal in Antarctica. Abstract : Human sewage disposal in Antarctica is leading to penetration of non-native Escherichia coli into endemic wildlife and facilitating gene pollution with antimicrobial resistance determinants.